English merchant shipping, 1460-1540 - Burwash, Dorothy (Univ. of Toronto Press, 1947)
Between 1460 and 1540 the development of merchant shipping was of vital importance to the growth of England as a European power. In this work Miss Burwash offers a complete history of the English merchant marine in the late middle ages and early renaissance period.